The Out of Darkness project - What makes an impactful digital storytelling tool? - Hallie Rodney; Shira B. Taylor; Ari Zaretsky; Raquel Ocvirk; Romy Shenderey (Psychiatry Research Communications, 2025)
Background: University students continue to suffer from mental illness at staggering rates. Currently, arts-based approaches have been found to increase mental health literacy in educational settings, such as universities. Specifically, digital storytelling interventions have shown promise in addressing mental health awareness and stigma related to mental illness. Methods: This study involves McMaster University students viewing a set of narrative films from the Out of Darkness project, followed by a semi-structured focus group discussion to determine what elements of the short films made them impactful. Thematic analysis was used to extract these themes. Results: The university students participating in this study identified the following three aspects that made the films impactful: connection to the films, the humanization of illness and the emotionality and vulnerability of the individuals depicted in the films. Conclusion: The results of this qualitative study suggest that digital storytelling interventions can be effective in addressing stigma surrounding mental health disorders and certain elements of narrative films allow for attitude change within the viewers.